Unravelling the Serbian Energy Transition Puzzle: Driving an Electric Vehicle Result in Higher CO2 Emissions than Driving a Traditional Internal Combustion Engine Counterparty - Sergey Fominykh; Dusan Stanar (Energija, Ekonomija, Ekologija)
This article delves into the intriguing paradox emerging in Serbia’s transportation landscape, where electric vehicles (EVs) are projected to generate more carbon dioxide (CO2) emissions than internal combustion engine (ICE) until 2030. Driving an EV within Serbia over the upcoming five years is estimated to contribute to roughly 25% more CO2 emissions compared to ICE vehicles. The study unveils the underlying factors behind this paradox, including Serbia’s energy mix dominated by lignite. By contrasting this with the European Union’s cleaner energy sources, the article underscores the delayed CO2 emissions reduction from EVs in Serbia. Furthermore, it explores the carbon footprint associated with EV production and highlights the challenges posed by the country’s energy infrastructure and vehicle fleet. The article concludes with insights into potential solutions, emphasizing the need for Serbia to accelerate its transition to renewables, aiming to align with 2030 targets, while parity with EU emissions levels is projected by 2040.